2008
DOI: 10.1159/000139638
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Oxidative Stress Biomarkers and Peritoneal Urea Clearance with Mitochondrial DNA Copy Number in Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: Background/Aims: The influence of oxidative stress and peritoneal clearance on alterations in mitochondrial DNA (mtDNA) copy number in continuous ambulatory peritoneal dialysis (CAPD) patients was investigated. Methods: Ninety-one CAPD patients (age, 30–57 years) and 99 age-matched healthy subjects were enrolled. Biochemical variables, plasma thiobarbituric-acid-reactive substances (TBARS), free thiol levels and mtDNA copy number in peripheral leukocytes were measured. Results: CAPD patients showed higher TBAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…For example, elevated oxidative stress in chronic peritoneal dialysis patients may lead to alterations in the mtDNA copy number in peripheral leukocytes [33]. In our current study, the mtSNPs listed in Table 3 were homoplasmic, as revealed by sequencing chromatograms (data not shown) [58][60].…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…For example, elevated oxidative stress in chronic peritoneal dialysis patients may lead to alterations in the mtDNA copy number in peripheral leukocytes [33]. In our current study, the mtSNPs listed in Table 3 were homoplasmic, as revealed by sequencing chromatograms (data not shown) [58][60].…”
Section: Discussionmentioning
confidence: 45%
“…The acquisition of ROS-induced mutations in CKD may be a consequence of increased oxidative burden in patients with chronic renal failure [9], [32], [33], [57]. For example, elevated oxidative stress in chronic peritoneal dialysis patients may lead to alterations in the mtDNA copy number in peripheral leukocytes [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in chronic renal failure cases the increased mtDNA content was identified in white blood cell. Although this disease is accompanied with high oxidative stress too, the inflammation is also involved [48] . The similarly increased mtDNA content also showed in septic shock, while testing the blood of patients [49] .…”
Section: Mtdna Content and Human Diseasesmentioning
confidence: 99%
“…15,16 A low mtDNA copy number correlates with increased oxidative stress and higher mortality rates in patients undergoing dialysis. In a uremic rat model, the mtDNA copy number was also significantly decreased compared to control rats, and was associated with decreased renal function.…”
Section: Introductionmentioning
confidence: 99%